Supporting caregivers of autistic children - Shivale, Shubham Jagannath (International Journal of Research in Medical Sciences, 2025)
I read with great interest the article by Abed et al on “Quality of life disparities among mothers of autistic children and mothers having normal children in Baghdad city-2024”. The study effectively demonstrated that mothers of autistic children face significantly poorer quality of life (QOL) compared to controls, with the greatest disparities noted in physical and psychological domains. These results highlight the immense caregiving burden borne by mothers, affecting their health, emotions, and daily functioning